(3JbSje GdNhGWQs - (3QhRHgGf Hf CHj GdfUQ GdaShj GdTjQGRj GdcGRQhfj, UOQ GdOjf, CHh eMeO GdHbdj,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi jSHM ai HMGQ eTjJg NhGWQ GdbdhH s
(3BNQgG (B:s
(3LYdfG Gddg hEjGce ef Cgd LhGQg bO Je GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B175s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs